Metformin sensitizes endometrial cancer cells to chemotherapy through IDH1-induced Nrf2 expression via an epigenetic mechanism. Issue 42 (18th October 2018) - Bai, Mingzhu; Yang, Linlin; Liao, Hong; Liang, Xiaoyan; Xie, Bingying; Xiong, Ji; Tao, Xiang; Chen, Xiong; Cheng, Yali; Chen, Xiaojun; Feng, Youji; Zhang, Zhenbo; et al.
Abstract Chemoresistance is the major obstacle to cure endometrial cancer, whereas metformin has demonstrated sensitization to chemotherapy in endometrial cancer. A novel finding states that isocitrate dehydrogenase 1 (IDH1) involves in cancer chemoresistance. Recent studies have revealed that epigenetic modifications facilitate chemoresistance. However, whether IDH1 play a role in metformin-induced endometrial cancer chemosensitivity through epigenetic modification is incompletely understood. Immunohistochemistry and Elisa assays were used to evaluate the expression pattern of IDH1 in endometrial tissue and serum, respectively. Western blot was performed to determine changes in expression of key molecules in the IDH1-ɑ-KG-TET1-Nrf2 signaling pathway after various treatments. Dot blot assays were used to assess global hydroxymethylation levels after metformin administration or plasmid transfection. Antioxidant response element (ARE) activity in the IDH1 promoter region was monitored by luciferase assay. Cancer cell sensitivity to chemotherapy was detected by SRB assay. We found that activation of the IDH1 signaling pathway in endometrial cancer tissue resulting from aberrant expression of IDH1 and its downstream mediators conferred chemoresistance. We found that this effect was abated by metformin treatment. Dot blot and HMeDIP assays revealed that metformin blocked IDH1-ɑ-KG-TET1-mediated enhancement of Nrf2 hydroxymethylation levels, eliminating chemoresistance. Moreover, we observed that chemoresistance was enhanced via a regulatory loop in which Nrf2 activated IDH1-ɑ-KG-TET1-Nrf2 signaling via binding to the ARE sites in the IDH1 promoter region. Our findings highlight a critical role of IDH1-ɑ-KG-TET1-Nrf2 signaling in chemoresistance and suggest that rational combination therapy with metformin and chemotherapeutics has the potential to suppress chemoresistance.